Sex(edness) in the City: Reimagining Our Urban Spaces With Abraham Akkerman - Gravador-Pancho, Duane Allyson U (Archīum Ateneo, 2019)
In this essay, Duane Allyson U. Gravador-Pancho foregrounds the gendered origins of the cities that we build. Taking her cue from Akkerman, Gravador-Pancho outlines the predominantly masculine characteristics of most cities, which coincides with the privileging of Western rationality that emphasizes rigidity and predictability in urban design. Such a predominantly masculine conception and design of the city comes at the cost of setting aside characteristics that are feminine, such as the elements of surprise and eroticism. But how would a city look like if we allowed the feminine to also come into play? “In the context of urban planning and city-building,” Gravador-Pancho claims, “the task is to reimagine spaces so as to make space for our bodiliness and eroticism, for our capacities to truly desire and love one another. The first aspect of this task consists in constructing spaces that acknowledge and encourage the use of our bodies for mobility, for reaching out. This would perhaps mean giving more space for walking, for sitting, for simply experiencing the city as a vulnerable human being among other vulnerable human beings, without the pretense to security that a car or any similar gadget provides.”